134k views
3 votes
SoIve the system of equations by elimination. (Addition)
1)-2x + 4y = -22
2x + 8y = –26

2 Answers

2 votes

Answer:

(3, - 4 )

Explanation:

Given the 2 equations

- 2x + 4y = - 22 → (1)

2x + 8y = - 26 → (2)

Adding the 2 equations term by term will eliminate the x- term, that is

12y = - 48 ( divide both sides by 12 )

y = - 4

Substitute y = - 4 into either of the 2 equations and solve for x

Substituting into (2)

2x + 8(- 4) = - 26

2x - 32 = - 26 ( add 32 to both sides )

2x = 6 ( divide both sides by 2 )

x = 3

solution is (3, - 4 )

User Mechanikos
by
5.2k points
4 votes

Answee:

We have these two equations:

-2x +4y =-22

2x + 8y -26

We need to try to get the same number multiplying both x or y, I think we can make the 2 of the first equation negative, for that, we multiply all the equation by -1:

2x + 8y =-26 ---- -2x - 8y =26

Now we have this:

-2x +4y = -22

-2x -8y = 26

Now e substract both equations:

-2x - (-2x) +4y -(-8y) = -22-26

12y = -48

Y = -48/12 = -4

And we replace to get x

-2x + 4y = -22

-2x +4*(-4)=-22

-2x - 16 = -22

x= -6/-2 =3

User Lyman Zerga
by
4.4k points